A highly sensitive pressure sensor using a double-layered graphene structure for tactile sensing. Issue 27 (22nd June 2015) - Chun, Sungwoo; Kim, Youngjun; Oh, Hyeong-Sik; Bae, Giyeol; Park, Wanjun
Abstract : A sensor adopting the electromechanical characteristics of single-layered graphene recognizes surface morphology. Tactile sensing for the sensor is demonstrated on the frequency scale of human perception induced by gentle touching. Abstract : In this paper, we propose a graphene sensor using two separated single-layered graphenes on a flexible substrate for use as a pressure sensor, such as for soft electronics. The working pressure corresponds to the range in which human perception recognizes surface morphologies. A specific design of the sensor structure drives the piezoresistive character due to the contact resistance between two graphene layers and the electromechanical properties of graphene itself. Accordingly, sensitivity in resistance change is given by two modes for low pressure (−0.24 kPa −1 ) and high pressure (0.039 kPa −1 ) with a crossover pressure (700 Pa). This sensor can detect infinitesimal pressure as low as 0.3 Pa with uniformly applied vertical force. With the attachment of the artificial fingerprint structure (AFPS) on the sensor, the detection ability for both the locally generated shear force and actual human touch confirms recognition of the surface morphology constructed by periodic structures.